A ressignificação do mito no pensamento do filósofo brasileiro Vicente Ferreira da Silva - SANTOS, Thiago Diniz (2019)
Resignify the myth is nothing more than to return to its original religious meaning. Vicente Ferreira da Silva is a Brazilian philosopher in full discovery who offers a solid platform to enter into this subject. In terms of a resignification, it is assumed that the religious meaning of the myth has somehow lost its relevance and that the purpose of this work is to uphold that meaning. The loss of this identity appears in the form of fables, projections of the unconscious, literature, etc., all of which are based on the common element of anthropomorphism. The question for what led to the loss of the primeval meaning of myths will require a whole historical contextualization that will permeate the introductory generalities of myths, their refusals, methodological approaches and conceptual elucidations. Importing also turn on the contextualization with points of Vicente Ferreira's, thought, thus maintaining a cohesion between chapters. The next step is to lay the foundations of Vicente philosophical thinking which will be based primarily on the influences of Martin Heidegger and Friedrich Schelling. Heidegger, from the turn of his late thought, will offer among his contributions his conception of Poetry as settingitself-to-work of truth of the Being, raised from two bibliographies, especially, the Letter on Humanism (1949) and the Origin of the Work of Art (1950). Schelling, on the other hand, will offer the conception of myths as the Theogonic Process of history radiated from two works referring to the last and most unknown phase of his thought, namely Philosophy of Revelation (1841/1842) and Historical-Critical Introduction to the Philosophy of Mythology (1842). Finally, the final destination of this work rests on the Philosophy of Religion, of Vicente Ferreira da Silva, the most original part of his philosophical trajectory. The nucleus of his thesis consists in the approximation between the last Heidegger and the philosophy of Schelling's mythology, bringing the Heideggerian unveiling of the being, not as poetry simply, but as Proto-Poetry, that is to say, Mythology (Religion).